Comparison of closure occlusal force parameters in post-orthodontic and non-orthodontic subjects using T-Scan® III DMD occlusal analysis. Issue 6 (1st November 2016) - Qadeer, Sarah; Yang, Lili; Sarinnaphakorn, Letrit; Kerstein, Robert B.
Abstract : Objective: Balanced occlusal force distribution is a critical factor for restorative, prosthetic or orthodontic treatment. It has been postulated that orthodontic treatment may lead to occlusal discrepancies in the arch due to changing the occlusal relationships. This study was conducted to compare the occlusal force parameters between natural dentition patients and a post-orthodontic treatment group. Method and Materials: Fifty Thai subjects were divided into non-orthodontic and post-orthodontic groups comprised of 25 subjects each (mean age 24.8 years). The T-Scan® III computerized occlusal analysis system was used to record a multi-bite closure for each subject. The initial occlusal contact location, the bilateral percentage force distribution, the percentage force in the anterior and posterior quadrants, and the individual tooth force percentages were calculated for both groups. The Student's Paired t -Test compared the in-group differences, while a one-way ANOVA analyzed the differences between the two groups. Results: The initial tooth contacts in both groups were found on the second molars and central incisors. Maximum force was most frequently observed on the left second molar tooth (15.9% non-orthodontic; 25.4% post-orthodontic). The bilateral right-to-left side force distribution (51.36% right–48.96% left) was not statistically different for all subjects, nor was it statistically different between the non-orthodontic (48.67% right–51.36% left) and the post-orthodontic groups (48.96% right–51.05% left). Statistically significant differences were found between the quadrants in both the groups (22.46% anterior–77.57% posterior in non-orthodontic subjects; 10.58% anterior–89.42% posterior in post-orthodontic subjects) ( p < 0.01). Conclusion: A significant occlusal force discrepancy was found in the post-orthodontic subjects, with higher force percentages observed posteriorly and much less percentage force anteriorly, when compared to the natural dentition subjects. T-Scan® III digital occlusal analysis may be recommended for orthodontic case finishing, to make visible to the clinician the severity of the orthodontically created occlusal force imbalance, such that it can be minimized during orthodontic case finishing.